Efek suplementasi kombinasi bawang putih, jahe merah, dan beras ragi merah (BJR-22) terhadap kadar kolesterol LDL pasien stroke dengan dislipidemia - Lieliesnaini Octaviariani Sutoyo; Rihadatul Aisy; Dicky Rinaldi; Retnaningsih Retnaningsih; Santoso Jaeri (Poltekkes Kemenkes Aceh, 2023)
Background: Stroke is the second leading cause of death worldwide, a significant contributor to disability, and the leading cause of stroke prevention by controlling risk factors. Dyslipidemia is a high risk of plaque buildup in the cell wall. An alternative search must be performed to prevent recurrent stroke events and to improve survival without disability. Nutraceuticals such as garlic (Allium sativum), red ginger (Zingiber officinale Roxb. var. rubrum Rosc.), and red yeast rice (Monascus purpureus) contain active compounds that inhibit HMG-CoA activity and limit the rate of cholesterol synthesis.Objectives: To analyze the effect of red ginger, garlic, and red yeast rice on low-density lipoprotein cholesterol (LDL-C) levels in ischemic stroke patients with dyslipidemia.Methods: Quasi-experimental research was conducted in a double-blinded manner. The study was conducted on outpatients at the Neurology Clinic of Dr. Kariadi Hospital Semarang, Central Java, from September to December 2022. Forty subjects with ischemic stroke and dyslipidemia were divided into intervention (20 subjects) and control (20 subjects) groups using consecutive sampling techniques. The intervention was conducted for 30 days. The intervention group received supplementation with a combination of garlic 225 mg, red ginger 125 mg of red ginger, 250 mg of 3x/day and statin for 30 days, while the control group received a placebo and statin. Lipid profile measurements were conducted at the Central Lab of Dr. Kariadi Hospital, Semarang, India. Data were analyzed using Fisher-Exact, Wilcoxon, and paired t-tests at a 95% CI.Results: The average LDL level before intervention was 152,0 ± 58,54, and after the intervention was 89,0 ± 27,07 (mg/dL). Before the intervention, The intermediate cholesterol level was 207,6 ± 37,6 to 164,5 ± 45,58. There was a significant improvement in LDL-C (p= 0,000) and cholesterol (p= 0,001).Conclusion: Supplementation with a combination of garlic, red ginger, and red yeast rice is effective in reducing LDL cholesterol levels